PENGELOLAAN TEKNOLOGI PENDIDIKAN DAN PENERAPANNYA PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SMK BUNGA PERSADA CIANJUR (Tarbawi : Jurnal Pendidikan Islam, 2023)
The management of educational technology plays a very important role in learning Islamic religious education. In the context of Islamic religious education, educational technology involves the use of relevant hardware and software to improve the quality of teaching, learning, and students' understanding of the Islamic religion. As such, technology can be an invaluable tool in enriching Islamic religious education and preparing students for the challenges of the modern world. This study uses a qualitative approach with case study-type research. In this study, the sources of data were: First, primary data sources, which are original sources, namely the Principal, Deputy Head of curriculum, and Islamic Religious Education teachers, While the secondary sources in this study are the sources of data in the form of books, journals, and magazines, The data collection techniques are observation, interviews, and documentation. The analysis technique uses data reduction steps, data display, and data conclusions. The results of this research are the Management of Educational Technology in Islamic Religious Education Learning, namely by involving the use of technology in the learning process, both in material stimulus, interaction between teachers and students, evaluation, and the development of teaching materials. The application of the technology is by adapting the technology to what is in the RPP, such as the learning objectives, materials, media, methods, and character of the students, and the results of the Management and Application of Educational Technology, namely PAI learning, easier access to various learning resources, learning materials, and PAI materials from various sources. This helps students learn independently, deeply, and diversely, not limited to textbooks or limited material in class, and also allows students to interact more directly with the subject matter.